Solar Greenhouse as an Energy Alternative Solution for Growing Vegetable in High Altitude Region: A Case of Baragaon, Mustang - Pandey, Dip (Journal of the Institute of Engineering, 2020)
In cold and dry high desert climate such as in Mustang, Manang or Dolpa growing green vegetables is a challenging task despite solar radiation throughout the whole year. Harsh and snowy winter, turbulent wind, limited availability of arable lands and water impedes plant growth. Solar greenhouse (SGH) is a renewable energy-based alternative for growing vegetables in these zones round the year in surplus quantity. At present, a large quantity of vegetables is purchased from nearby market towns (Pokhara and Beni) at double the price. Promotion of greenhouse vegetable farming has not only potential to relieve local people from such financial burden but can even create new business opportunities. As vegetables produced at these altitudes use only organic manure, their quality is desirable for a market where demand for organic products is constantly increasing. From a literature study of SGH cases in Ladakh, Humla and Khumbu region it was found that varieties of vegetables could be grown even during winter when temperatures drop to -25°C. For instance, owners of specially designed SGHs in Ladakh ate eight times the volume of vegetables they had eaten prior to acquiring these SGHs and have seen their incomes rise by 30%. The following article presents a study on SGH possibilities for vegetable farming in the Baragaon rural municipality of Mustang district, applying methods such as observations, informal interviews and stakeholder inclusion. Currently, there exists only rudimentary samples of plastic greenhouses in most villages, where only green leafy vegetables grow during winter. During summer, vegetable growth is conducted in open fields rather than inside the greenhouses. This is mainly due to their overheating caused by lack of ventilation. In Chhengor, one of the villages in Baragaon, organic farming is already taking a promising leap towards organic vegetable business. After discussion with farmers and other stakeholders appropriate design of SGH seems a good solution for durability of SGH structure and to ensure that varieties of vegetables grow in surplus quantity round the year. The article presents possibilities for SGH design and discuses factors for SGH establishment such as affordability, monitoring and maintenance. Additionally, it pinpoints infrastructural support such as agriculture policy at local level, for example in forms of subsidies and training of farmers to grant successful implementation of SGH approaches for high altitude settlements.